Photoelectron momentum distributions with twisted attosecond X waves carrying orbital angular momentum - Zhang, Xiaofan; Ma, Xiaomeng (Frontiers in Physics, 2023)
We theoretically investigate the photoelectron momentum distributions of 1s and 2px,y states of hydrogen by twisted attosecond X waves carrying orbital angular momentum based on first-order perturbation theory. The photoionization spectra as a function of photoelectron energy and emission angle are analyzed respectively. The results indicate that there are interference fringes in the energy spectra and more nodes in the angular distributions. These angular nodes are attributed to both orbital structure and the temporal-spatial structure of X waves. We derive an equation that can quantitatively describe the angular nodes in the photoelectron angular distributions. Our results and analyses indicate that the angular distribution is an important observation for the investigation of the information of both orbitals and X waves.